Effect of rate and source of phosphorus application on soil organic carbon pools under rice (Oryza sativa)-wheat (Triticum aestivum) cropping system - DHRAM PRAKASH; D K BENBI; G S SAROA (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted during 2006-2013 on rice (Oryza sativa L.) - wheat (Triticum aestivum L.) cropping system at research farm of Punjab Agricultural University, Ludhiana, India. The study aimed to evaluate the effect of two rates of phosphorus (P) application, viz. 0 and 30 kg P2O5/ha to rice in rice-wheat sequence on soil organic C pools. Phosphorus was applied through either single super phosphate (SSP) or rock phosphate (RP) with and without farmyard manure (FYM). After 7 years of cropping total organic carbon (TOC) and labile C fractions were higher under FYM and RP treated plots and the lowest in unfertilized control. Plots treated with FYM and fertilizer-P either individually or in combination significantly (P<0.05) increased TOC and water extractable organic C (WEOC) in surface (0-7.5 cm) and subsurface (7.5-15 cm) soil. Beneficial effects of fertilizer-P application through RP were lower than SSP. Potassium permanganate oxidizable C (KMnO4-C) comprised the largest labile pool of soil organic C and represented 13.6% of TOC. Carbon management index (CMI) improved with FYM and fertilizer-P applications indicating the favorable impact of these treatments on C stabilization in soil. Conjoint application of FYM and RP improved soil organic C pools to a greater extent than their individual application, suggesting the need for integrated use of FYM and RP in these alluvial soils.